The Effect of Sodium Selenite on Fertility of Albino Male Mice Treated with Hexavalent Chromium (Baghdad Science Journal, 2013)
This study was conducted to determine the effect of sodium selenite (0.5 mg/kg ) on fertility of mature albino mice treated with hexavalent chromium (1000 ppm) . 32 mice were divided into four groups : control group / group exposed to hexavalent chromium (1000 ppm) / group treated with sodium selenite (0.5 mg/kg) and exposed to hexavalent chromium (1000 ppm) / group treated with sodium selenite (0.5 mg/kg) alone . The experiment lasted for 35 day . The results showed a significant (P < 0.05) decrease in sperm motility , concentration , percentage of live sperm and testosterone concentration with a significant (P < 0.05) increase in the percentage of abnormal sperm in group treated with hexavalent chromium in comparison with control group . The results also showed a significant (P < 0.05) increase in sperm motility , concentration , percentage of live sperm and testosterone concentration with a significant (P < 0.05) decrease in the percentage of abnormal sperm in group treated with Sodium selenite and exposed to hexavalent chromium in comparison with group exposed to hexavalent chromium . The group treated with Sodium selenite alone showed an improvement in all parameters studied except the percentage of abnormal sperms which showed a significant (P < 0.05) decrease .